External and internal factors on the class and gender relations of the Tumandok of Central Panay - Edaniel, Karen G.
Scattered around the country are the different indigenous communities. Resident in the islands since long before the Spanish colonization. They were force to flee in the hinterlands due to bigotry and hostility inflicted on them by the colonialist. Until now, these different Indigenous communities continue to live on with their traditions and culture as they become to endure for their existence and struggle for recognition by the government., The luscious, green mountains of Panay are dwelling places of about 40,000 indigenous peoples, among different communities. Aptly referred to as the Tumandok or "natives". Their main source of livelihood is Kaingin (swidden farming). They possess a distinctively rich culture that has withstood influences from the lowlands. For a long time, the government has neglected them, and they do not have access to basic social services. Large tract of these lands have been taken away from them, as military reservation areas were set up along the borders of Tapaz and Jamindan, Capiz. About twenty indigenous communities are covered by the military reservation. This research has four objectives: First, is to trace the origins and characterize the traditional socio-economic organization of the Tumandok around the boundaries of the towns of Tapaz and Jamindan, Capiz. Second, is to characterize and identify the shifts in the class and gender relations among the Tumandok. Third to characterize and distinguish the internal and external factors affecting the class and gender relations of the Tumandok. And lastly, to identify the outcomes of the changes in class and gender relations. From the study's conclusions are recommended courses of action for community leaders and external agencies that impinge upon their lives. Out of the twenty Indigenous Communities covered by the military reservation area, we selected five villages namely: Barangays Tacayn, Daan Sur, Mabini, Carvasana and Sitio Pula. Our main interviewees were members and leaders of the People's Organization of those five areas. The investigation reveal s the specific activities that have brought negative changes on the situation of Tumandok. We found out that external factors namely: militarization and globalization, has intensified the worsening condition of the internal problems of the Tumandok namely: economic, education, health problem and cultural condition. There are also positive changes from the external factor namely the NGOs and the internal factor of establishing POs in the villages, though the changes in class and gender relations is fairly negligible. Internal to Tumandok, there is no highly stratified class relation. Militarization lessens their access to their ancestral domain, hence making their life miserable. Despite the shift from kaingin to permanent farms and improvement of farm implements, their produce cannot sustain their subsistence. There has been no marked changes in gender differentiation among the Tumandok community. due to their impoverished conditions, women's roles are not confined to reproductive work only but extend to production as well. Womena are given more room to participate in decision making and sustaining their subsistence.